Matching customer expectations and perceptions in e-commerce - Archer, Norman P.; Head, Milena M.; Yuan, Yufei; McMaster University, Michael G. DeGroote School of Business (My University, 2001)
In addition to lack of physical infrastructure, there are other unrelated barriers to the growth of e-commerce. These result from the unwillingness of customers to engage in online transactions even if the infrastructure is in place. In this paper we discuss a number of these issues, including particularly lack of trust, and propose a model that links the components of the customer-vendor relationship logically. The model provides a structure to analyze and potentially mitigate the causes of the gap between customer expectations from online commerce and their perceptions of what the vendor offers.
17 leaves : ; Includes bibliographical references (leaves 16-17). ; "February, 2001";
This research was supported financially by the Social Sciences and Humanities Research Council of Canada.
Keywords: Trust; Electronic commerce; Model; Customer expectations; Customer perceptions; Business; Business; Electronic commerce > Effect of consumer behavior on Electronic commerce > Customer services Consumer confidence